Generations in context: the development of a new approach using Twitter and a survey - Peretz, Hilla; Fried, Yitzhak; Parry, Emma (Wiley, 2021)
Millennials (born between 1982 and 1999) and their work-related values have received significant attention in recent years, but empirical evidence of Millennials’ characteristics is inconclusive. One possible reason behind these mixed results is the tendency to apply generational groupings universally and ignore the potential impact of the broader context, such as national culture. This study develops a contextual perspective on generational differences and proposes a new, hybrid approach to generations. First, we conducted an exploratory study using data mining of big data from Twitter, to test hypotheses regarding differences between age cohorts in four different countries (The United States, Russia, India, Argentina). Second, we conducted a follow-up study to further investigate the between-countries differences found in the first study, using survey data from the same four countries. The results highlight the importance of both global and local influences when considering generational differences, supporting a new hybrid theoretical approach to understanding generational differences. Millennials were shown to be different from Generation X (born 1965–1981) across countries in relation to the behavioural aspect of writing style on social media. In contrast, in relation to work values, generational groupings were not universal, as the distinction between the work values of Millennials and Generation X was only found in the individualistic culture of the United States, and not in other, more collectivistic, cultures.
Keywords: Millennials; Work-values; Data mining; national context